A Study on the Seasonal Periodicity of Diatoms with Relation to Silica in the Phytoplankton of a Dam Lake in Turkey - Alp, M. T.; Sen, B. (Medwell Online, 2010)
In this study, diatoms occurring in the phytoplankton of Cip Dam Lake were investigated between September 1994 and 1995. Individual numbers of diatom taxa were obtained by counting 1 mL of phytoplankton sample and results were expressed as cells mL(-1). Water samples for chemical analyses were filtered immediately and concentrations of silica were determined spectrophotometrically. A total of 120 taxa were recorded; Navicula (24 taxa) and Nitzschia (19 taxa) were the genera represented by most species. Of all, Achnanthes minutissima, Cyclotella meneghiniana, C. kutzingiana, C. ocellata, Fragilaria brevistriata and F. pinnata were the most conspicuous diatoms with respect to both frequency of occurrence and number of individuals. Although, diatoms occurred in considerable numbers in almost every season their best growth was recorded in spring.
Keywords: Diatoms; phytoplankton; concentration; compicuous; frequencu; spring